A parallel algorithm for geoprocessing of vegetation indices - Albert G. Saribekyan (Изд-во НАН РА)
Geographic information systems (GIS) play a vital role in environment-related issues, from which well-known is the calculation of vegetation indices (VI) using the satellite images. In this paper a parallel algorithm for geoprocessing of VI’s is introduced with appropriate benchmarkings, which were performed using high- performance computing (HPC) resources.
Keywords: Mathematics; Algorithm